Evaluación de los procedimientos técnicos administrativos para las inspecciones por caso de delitos contra los bosques o formaciones boscosas, en la provincia de San Martín - Aguila Ynga, Vanny Del (2014)
This research work is justified, since the expert evaluation, carried out to date by competent bodies, for cases of crimes against forests or forest formations, intends to make an administrative technical procedures manual, allowing you to standardize the conduct of the surveys for cases of crimes against forests or wooded formations~ which facilitates effectively to protecting forests, preventing and repairing damage caused by deforestation, of which having as objectives review, analyze and contrast legal technical reports, issued by the experts in environmental, for cases of crimes against forests or forest formations, conducting field inspections: in the districts of Chazuta (Sector Aguano Muyuna and land two brothers)~ La Banda de Shilcayo district (Sector Metozapa, community of Polish and Sector San Juan, village Sinamipampa)~ Barranquita district (High Ushpayacu and Italy new Sector), district of Pinto Recodo (village Jesus del Monte and sector Juanjuicillo ). Of all inspections carried out in the Chazuta district, Banda de Shilcayo Barranquita and Pinto Recodo, it noted and 1 check clearing, burning and destruction of forests (primary and secondary)~ obtaining, 1.5ha deforested Chazuta district~ 5.5ha deforested in the districts of Banda de Shilcayo~ 24. 75ha deforested in Barranquita district and 4.5ha deforested in the Pinto Recodo District All these illegal acts committed against forests, generated the loss of plants, bacteria, orchids, fungi, protozoa in deforested areas. When the forests are deforested (logging, burning and destruction), the soil stays without the protection from the elements and there is a large loss of biodiversity Of all inspections conducted in the field, by the competent authority, is issued the Legal technical report, correspondent of each case to the Special Prosecutor in the environmental field, to continue with the respective investigations of the case, regarding the legal technical report